2019
DOI: 10.3390/ani9060362
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Dietary Supplementation of L-Carnitine and Excess Lysine-Methionine on Growth Performance, Carcass Characteristics, and Immunity Markers of Broiler Chicken

Abstract: L-carnitine as well as lysine and methionine are amino acids of important nutritional and nutraceutical interest and are used in nutritional strategies as dietary supplements to improve feed quality characteristics in animals and broiler chicken in particular. This study investigated the effect of different levels of L-carnitine and extra levels of lysine-methionine on growth performance, carcass characteristics, and some immune system markers. Two hundred seventy male Ross 308 broilers were a fed control diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 55 publications
2
28
1
Order By: Relevance
“…L-carnitine and excess lysine and methionine in the diet did not affect feed intake in starter birds but in finisher birds it did. L-carnitine supplementation had no effect on IgM titer but had an effect on serum antibody titers in broilers vaccinated against Newcastle disease and Gumboro's disease (Ghoreyshi et al 2019).…”
Section: Advances In Delivery Of Nutraceuticalsmentioning
confidence: 96%
See 2 more Smart Citations
“…L-carnitine and excess lysine and methionine in the diet did not affect feed intake in starter birds but in finisher birds it did. L-carnitine supplementation had no effect on IgM titer but had an effect on serum antibody titers in broilers vaccinated against Newcastle disease and Gumboro's disease (Ghoreyshi et al 2019).…”
Section: Advances In Delivery Of Nutraceuticalsmentioning
confidence: 96%
“…Nutraceuticals have been in focus in poultry science quite recently due to the nutritional and healthier properties of feed ingredients and the adverse effects of chemical pharmaceuticals like antibiotic resistance and drug residues (Elnesr et al 2019a(Elnesr et al , 2020. Amino acids (Ghoreyshi et al 2019), minerals (Khatun et al 2019), and vitamins (Ahmad et al 2019) which are common ingredients of poultry ration or a combination of them (Moghaddam & Emadi 2014; Horvath & Babinsky 2018) can be nutraceuticals, especially important in poultry feeding. Generally, poultry receives nutrients through the consumption of natural feedstuffs, but some key essential amino acids (lysine, methionine, threonine and tryptophan), vitamins and minerals are often offered as synthetic supplements (Ravindran 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, with the increasing demand for poultry meat and eggs, nutraceuticals are used as dietary supplements to improve feed quality characteristics in poultry. Recently, many studies have reported that dietary supplementation with L-carnitine ( Ghoreyshi et al., 2019a , Ghoreyshi et al., 2019b ; Ghoreyshi et al., 2019a , Ghoreyshi et al., 2019b ), quercetin ( Goliomytis et al., 2014 ), and saponins ( Bera et al., 2019 ) in broiler chickens improves meat quality. In addition, dietary supplementation with spirulina ( Omri et al., 2019a , Omri et al., 2019b , Omri et al., 2019c ), linseeds ( Omri et al., 2019a , Omri et al., 2019b , Omri et al., 2019c ), and fenugreek seeds ( Omri et al., 2019a , Omri et al., 2019b , Omri et al., 2019c ) has successfully improved the egg quality of laying hens.…”
Section: Introductionmentioning
confidence: 99%
“…Omega-3 fatty acid rich food has been shown to be correlated with a lower incidence of CVD [ 2 ]. Enrichment of chicken carcasses with omega-3 fatty acids [ 3 ], so-called functional foods, is an important research arena in human and animal nutrition. Advantageously, chicken meat contains high protein and low saturated fat [ 4 ] and this is the reason for its nomination as a good functional food.…”
Section: Introductionmentioning
confidence: 99%